Rethinking Religious Influence on Mathematics Learning Behavior: A Mathematical Model of Planned Behavior amid Shifting Educational Paradigms - Crismono, Prima; Hudi, Saman; Ilyas , Muhammad; Yanuardianto , Elga; Dahri , Harapandi; Yakoh, Mahnawawe (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat - Islamic Institute of Syarifuddin Lumajang, Indonesia., 2025)
Amid evolving educational paradigms that demand greater inclusivity and cognitive adaptability, this study reexamines the influence of religion on students’ mathematics learning behavior through the lens of the Theory of Planned Behavior (TPB). A mathematical model was developed to analyze how religious values moderate the interplay between attitudes, subjective norms, and perceived behavioral control in shaping students' intentions to engage in mathematics learning. The study employed a mixed-methods design, integrating structural equation modeling of survey data with qualitative thematic analysis of interviews conducted in culturally diverse elementary school settings. Findings indicate that religion significantly amplifies the positive effects of motivational and normative constructs on learning intention, particularly among students with strong religious orientations. While religiosity fosters greater discipline and perseverance in mathematical tasks, the study also reveals that certain conservative interpretations may restrict creative and critical thinking, thus posing challenges to problem-solving flexibility. These results call for a nuanced pedagogical approach that respects students’ belief systems while promoting open-ended mathematical reasoning. This research contributes to the broader discourse on culturally and religiously responsive education and offers insights for future curriculum reforms that align value-based education with cognitive development goals